Compensation management and employee performance: Culinary business organizational Roti Bakar 234 Bandung - Wicaksana Gara, Gd Pandya (Universitas Pendidikan Nasional, 2025)
Internal organization is a crucial aspect for every firm in achieving its objectives, and the culinary business is no exception. Roti Bakar 234 Bandung is a culinary business that has been operating since 1970. Therefore, maintaining its internal condition is essential to sustaining a competitive advantage in the long term. The archetypal model is a concept used to analyze broad patterns rather than narrowly defined organizational features, in order to better understand organizational structure, management, and internal conditions. This study aims to examine the internal condition of Roti Bakar 234 using the archetypal model. The method employed was a questionnaire survey involving 20 employees, focusing on four dimensions: leadership-driven, market focus, knowledge core, and execution edge. The findings show that the average score for leadership-driven is 3.84, market focus is 3.90, execution edge is 3.66, and knowledge core is 3.64. The lowest score is in the knowledge core (3.64), specifically in the area of rewards and incentives.